A spatial planning approach for the sustainability of provisioning ecosystem services with economic value: The case of Türkiye - Karadeniz, Enes; Sekeroglu, Ahmet; Kaya, Asur Yuksel; Zhang, Maomao; Adiguzel, Fatih (Academic Press Ltd- Elsevier Science Ltd, 2026)
Provisioning ecosystem services are closely associated with climate change and land use. Therefore, spatial planning approaches are essential for the integration and sustainability of provisioning ecosystem services. This study aims to propose a spatial approach for integrating economically valuable provisioning ecosystem services into planning processes based on environmental sustainability. In this context, the study area includes 26 regions in T & uuml;rkiye classified according to the NUTS Level 2 system, which features rich biodiversity. The analysis evaluates 15 different taxa of economically valuable provisioning ecosystem services, including herbal medicine, meadow-pasture plant, food, landscape plant, genetic material fauna, genetic material flora, bee plant, complementary medicine, herbal tea, ornament fauna, ornament flora, essential oil, livestock, spice, and fishery. To assess the spatial clustering, distribution, and hotspots of these taxa in an integrated manner, a spatial statistical model was implemented by combining Global Moran's I, Local Moran's I, and Getis-Ord Gi* statistics using ArcGIS Pro, one of the key Geographic Information System (GIS) application tools. The results indicate statistically significant findings in 12 taxa, with strong spatial dependencies observed in medicinal plants (Moran's I: 0.28), genetic material flora (0.22), and genetic material fauna (0.20). Furthermore, regions such as TR51, TR52, TR61, and TR62 exhibit high spatial clustering tendencies and should therefore be prioritized in spatial planning hierarchies from an environmental sustainability perspective. The study provides actionable insights for decision-makers through a spatial planning and assessment approach aimed at integrating ecosystem services into regional sustainability efforts.
Keywords: Provisioning ecosystem services; Regional biodiversity; Spatial portal; Spatial planning; Policy integration; Regional scale